2006
DOI: 10.1097/01.smj.0000242786.23314.fd
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Treatment with Infliximab on Anticyclic Citrullinated Peptide Antibody and Rheumatoid Factor in Patients with Rheumatoid Arthritis

Abstract: Treatment with infliximab results in decreased anti-CCP antibody and IgA-RF early in the course of therapy that is not sustained. IgM-RF declines and remains decreased for at least 54 weeks. Investigations in larger cohorts of RA patients (especially early RA) with longer follow-up are needed to assess the impact of specific therapeutic interventions on anti-CCP antibody and RF levels and the relationship of their levels to disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This observation probably reflects the uncontrolled clinical course of the disease in this series since it is known that rheumatoid factor levels tend to decrease when the disease moves towards remission (27).…”
Section: Discussionmentioning
confidence: 97%
“…This observation probably reflects the uncontrolled clinical course of the disease in this series since it is known that rheumatoid factor levels tend to decrease when the disease moves towards remission (27).…”
Section: Discussionmentioning
confidence: 97%
“…Also Ahmed and colleagues 119 found that the serum levels of anti‐CCP antibody decreased significantly during 30 weeks of infliximab therapy. However, the decrease was not significant at week 54.…”
Section: Effect Of Therapy On Anti‐ccp Statusmentioning
confidence: 96%
“…First anti-CCP titer is unchanged by anti-TNF-α treatment, 9,10 second its treatment results in a decrease in anti-CCP titers, 11 and third anti-CCP decreases at 6–7 months but returns to the baseline. 12 The difference among these reports can not be explained although many investigators have highlighted the significant variations in anti-CCP titers among patients treated with anti-TNF-alpha drugs. Additionally, the prognosis for joint damage remains obscure in the patients, whose anti-CCP titer was not decreased by anti-TNF-α drugs treatment.…”
Section: Discussionmentioning
confidence: 98%